Dental Busy Book Media on Improving Tooth Brushing Skills - Aldila, Aldila (Center of Excellent (Pusat Unggulan Iptek), 2025)
Background: Learning while playing is favored by elementary school students to improve student skills, one of which is the dental busy book game. The material in this game is formed in a book presented in the form of pictures and is equipped with a description of the picture. Objective: The purpose of this study was to determine the description of the skills of how to brush teeth before and after counseling with dental busy book media in grade I SDIT Tirta Buaran Serua Ciputat South Tangerang. Methods: This research method is quasi experimental research with a purposive sampling technique of 34 first grade children. Data collection instruments used were pre and post test observation sheets totaling 10 activities and dental busy book counseling media. Results: The results of this study obtained skills before counseling which included the highest category with unskilled criteria as many as 20 people (58.8%) and the lowest category with skilled criteria as many as 14 people (41.2%). While after counseling the results obtained with the highest category with skilled criteria as many as 34 people (100%), and the lowest category did not exist. The average tooth brushing skills of first grade children of SDIT Tirta Buaran Serua Ciputat South Tangerang increased from 7.26 to 9.71 with skilled criteria. Conclusion: It can be concluded that there is an increase in tooth brushing skills with counseling using dental busy book media